Phonological Change of Minangkabau Protolanguage in Tanjong Ipoh Isolect, Negeri Sembilan - Nadra, Nadra; Aslinda, Aslinda; Zikri, Ahmad (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
The traces of the Minangkabau language in Negeri Sembilan are evidence that the Minangkabau people not only migrated to the coastal areas of Sumatra but also to the Malay Peninsula. Despite historical evidence linking the Tanjong Ipoh isolect to Minangkabau, the extent of phonological change in this isolect remains undocumented. This study seeks to bridge this gap by systematically analyzing phonological evolution. This study aims to describe the forms and types of phonological changes observed in the Tanjong Ipoh isolect, located in Kuala Pilah, Negeri Sembilan, Malaysia. Data were collected through observation and interviews. We interviewed three native speakers of the Tanjong Ipoh isolect, selected through purposive sampling based on linguistic competence and community recognition, who participated in this study. Additionally, we also interview various speakers to help validate the data. We documented the data using both note-taking and recording techniques. We conducted the analysis using a top-down approach by identifying Minangkabau protolanguage (PBM) reflexes in the Tanjong Ipoh isolect. The results are that the vowels that have changed in Tanjong Ipoh isolect are *i, *u, *ə, *e, and *a, while PBM consonants that have changed in Tanjong Ipoh isolect are *t, *k, *s, *R, and *l. PBM consonant changes in the Tanjong Ipoh isolect consistently occur in environments where PBM vowels also change. The study concludes that all sound changes observed in the Tanjong Ipoh isolect are conditioned. Among the types of changes, lenition (weakening) is the most prevalent, with additional changes including assimilation, dissimilation, fortition, diphthongization, splitting, merging, and elimination. The findings align with established phonological theories and contribute to understanding language evolution in migrant communities.